From inclusion to acknowledgment: a paradigm shift - Argento Nasser, Ana (Equality, Diversity and Inclusion: An International Journal, 2024)
PurposeThis article aims to provide a new paradigm for thinking about disability, which can be applied to other social groups, historically invisible and whose rights have been violated. The Model of Communication and Legitimate Acknowledgement of Disability (MCLAD) tries to break with the logic of continuing to add terms and euphemisms around the issue. The author proposes a new line to think about relationships in democratic societies. Taking the step from inclusion to acknowledgment does not imply another way of naming the disability, but rather addressing the problem from concrete practices of recognition. In order to arrive at the proposal of the MCLAD, the author will make a journey that addresses how disability has been understood throughout history, according to the study of different authors.Design/methodology/approachDisability has been perceived over time in many different ways, which led some authors to build models in order to explain certain social approaches to the subject. This article traces a journey from the first model to the present. In turn, it proposes a new one: the MCLAD, which is characterized by a paradigm shift: moving from inclusion to acknowledgment. To substantiate this, three categories are presented: acknowledgment, distance and vulnerability. The different theories and concepts that support the model will also be presented. The purpose of the MCLAD is to deepen the idea of empowering people with disabilities as part of today’s diverse societies and closing historically constructed gaps which are still in force.FindingsThe MCLAD proposes three categories: acknowledgment, distance and vulnerability. In turn, in each of them, there is a link between three axes: person with disability/society/state, analyzing the dynamics of these relationships presented, will provide us with the necessary elements to understand the proposed turnaround.Research limitations/implicationsAlthough the different models will be presented according to the chronological order of definition over time, all of them still coexist today, in many cases in hybrid and naturalized ways in social practices. Recognizing what practices and conceptions are behind each model, allows us to recognize and resignify the ways of communicating toward people with disabilities (PWD) and on the issue of disability. It also allows other specific recognition practices, such as the legitimization of public policies from the laws that protect them.Practical implicationsTo replace the paradigm of inclusion for that of acknowledgment and to recognize how the three categories (acknowledgment, distance and vulnerability) are linked with the three issues (PWD – society and state) allowing specific relationship and practises of legitimate or not acknowledgement. When the author affirms that the MCLAD implies a paradigm shift, the author means that it provides some elements from legitimate acknowledgment to complement aspects which inclusion does not address, and that the other models did not take into account. These are: the self-acknowledgment of people with disabilities and the sense of responsibility linked to empowerment; vulnerability as a category of reconciliation, which is typical of every human being; the contribution of the Phenomenology of the Among to think about how relationships and practices actually occur in society and, finally, the role of the state, which must watch over all its citizens, avoiding the distance between discourse (laws) and practices and, above all, avoiding exclusion from the system due to lack of monitoring of actions.Social implicationsIt should be noted that the MCLAD starts from the idea of language as a constructor of realities and conceives communication as an enabler of the acknowledgment of the other, who is also subject to rights. At the same time, it vindicates the voice of people with disabilities as protagonists (“Nothing about us without us”) and fosters the need for PWD themselves to be active in their struggles, promulgating legitimate acknowledgment. At the same time, it points out that the empowerment of PWD implies not only that they are aware of their rights but also that they themselves know and fulfill their duties within the democratic societies of which they are a part of and which, at least discursively, are regulated by laws. In other words, being empowered is also being responsible for living in society.Originality/valueThe main contribution that the MCLAD has to offer is to replace the paradigm of inclusion for that of acknowledgment. And, throughout the path followed in this article, an attempt has been made to establish that the turnaround is not to capriciously install a new concept (acknowledgment), but to demonstrate that the new paradigm involves three categories that sustain and support a model that seeks to be the basis for effective public policies, for a society that values diversity and for people who feel worthy and contribute to dignify others.